Fatty acid metabolism in T-cell function and differentiation. (14th June 2022) - Endo, Yusuke; Kanno, Toshio; Nakajima, Takahiro
Abstract: Immunometabolism has recently emerged as a field of study examining the intersection between immunology and metabolism. Studies in this area have yielded new findings on the roles of a diverse range of metabolic pathways and metabolites, which have been found to control many aspects of T-cell biology, including cell differentiation, function and fate. A particularly important finding has been the discovery that to meet the energy requirements associated with their proliferation, activation and specific functions, T cells switch their metabolic signatures during differentiation. For example, whereas the induction of de novo fatty acid biosynthesis and fatty acid uptake programs are required for antigen-stimulation-induced proliferation and differentiation of effector T cells, fatty acid catabolism via β-oxidation is essential for the generation of memory T cells and the differentiation of regulatory T cells. In this review, we discuss recent advances in our understanding of the metabolism in different stages of T cells and how fatty acid metabolism in these cells controls their specific functions. Abstract : T-cell fatty acid metabolism Graphical Abstract: